Diagnosis of the Origin of Cardiomyopathies and the Advantages of Modern Clinical Diagnostic Methods - Yodgorov Yoqubjon Yodgor oʻgʻli; Lapasov Mexrojiddin Rabbimqul oʻgʻli; Norqulov Abdulaziz Gʻofur oʻgʻli (Journal of Science in Medicine and Life, 2025)
Cardiomyopathy is a primary lesion of the heart muscle, not associated with inflammation, tumor, ischemic genesis, its typical manifestations are cardiomegaly, progressive heart failure and arrhythmia. There are dilated, hypertrophic, restrictive and arrhythmogenic cardiomyopathies. As part of the diagnosis of cardiomyopathy, ECG, echocardiography, chest radiography, MRI and cardiac MSC are performed. For cardiomyopathies, a gentle regimen and drug therapy are prescribed (diuretics, cardiac glycosides, antiarrhythmic drugs, anticoagulants and antiplatelet agents); According to indications, heart surgery is performed.